2017
DOI: 10.1371/journal.pbio.2001154
|View full text |Cite|
|
Sign up to set email alerts
|

Ongoing neurogenesis in the adult dentate gyrus mediates behavioral responses to ambiguous threat cues

Abstract: Fear learning is highly adaptive if utilized in appropriate situations but can lead to generalized anxiety if applied too widely. A role of predictive cues in inhibiting fear generalization has been suggested by stress and fear learning studies, but the effects of partially predictive cues (ambiguous cues) and the neuronal populations responsible for linking the predictive ability of cues and generalization of fear responses are unknown. Here, we show that inhibition of adult neurogenesis in the mouse dentate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 75 publications
3
52
2
Order By: Relevance
“…Adult neurogenesis can be specifically inhibited, but this manipulation has few behavioral effects under baseline testing conditions. Complete inhibition of adult neurogenesis had no effect on NSF in this study, consistent with previous findings that new neurons only affect behavior in this test under stressful conditions (42; 43; 89). Adult neurogenesis also had no effect on sucrose preference, possibly because ablation of new neurons did not affect weight, as stress did.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Adult neurogenesis can be specifically inhibited, but this manipulation has few behavioral effects under baseline testing conditions. Complete inhibition of adult neurogenesis had no effect on NSF in this study, consistent with previous findings that new neurons only affect behavior in this test under stressful conditions (42; 43; 89). Adult neurogenesis also had no effect on sucrose preference, possibly because ablation of new neurons did not affect weight, as stress did.…”
Section: Discussionsupporting
confidence: 93%
“…These patterns do not demonstrate any causative relationship, they are consistent with current thinking on the effects of new neurons on hippocampal circuits and the causes of pyramidal cell dendritic atrophy. Young neurons appear to enhance excitability in the hippocampus (7478), and inhibiting neurogenesis can decrease overall hippocampal activity during unpredictable stress (42). Work on dendritic remodeling following stress suggests that CA3 pyramidal neuron atrophy results from glutamate excitotoxicity associated with DG hyperexcitability (26; 79), which could potentially be exacerbated by the presence of excitable new neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice without neurogenesis show increased anxiety‐like behavior for several days after acute or chronic stress (Anacker et al, ; Glover, Schoenfeld, Karlsson, Bannerman, & Cameron, ; Seo, Carillo, Chih‐Hsiung Lim, Tanaka, & Drew, ; Snyder et al, ). The current study found increased anxiety‐like behavior for at least 10 days after SPS regardless of the presence or absence of new neurons.…”
Section: Discussionmentioning
confidence: 99%